Relationship between socio-economic factors and participation in decision making in tourism industry among women in Zanzibar - Hassan Abdalla, Fadhila; Abuu Samah, Asnarulkhad; Hashim, Ahmad Hariza; Rosnon, Moh’d Roslan (Elsevier, 2022)
This study determined the relationship between socio-economic factors and participation in decision-making among women community in Zanzibar. Data was collected from 387 respondents using structured questionnaire distributed to nine wards of Zanzibar and analyzed using Smart PLS. The descriptive analysis revealed that there is a high level of participation in decision-making among women community in Zanzibar whereby the mean is equal to 3.8519, and standard deviation is 0.75238. The Smart PLS analysis results indicated that there are significant negative relationships between level of education, nature of tourism activities and participation in decision making. Hence, this result indicates that the less educated the women are the less they participate in the decision-making. Further, the nature of tourism activities is also negatively affecting the decision to participate in the decision-making process.